RANCANG BANGUN STORYTELLING GAME VISUAL NOVEL ALKITAB INJIL MATIUS - Aribana Depari, Boy; Care Khrisne, Duman; Arya Mertasana, Putu (Jurnal SPEKTRUM; Vol 10 No 1 (2023): Jurnal SPEKTRUM, 2023)
Bible is a Scripture that believed by Christians which used as foundation in religious life. Reading the Bible can be more enjoyable by combining text, images, and sound, namely by creating a visual novel game. This visual novel game can be made using Ren'py. By making this Visual Novel Game about the Bible, children can use games to learn about the Bible. The data in this study can be obtained through books, journals, and the internet which are related to the concepts and research methods being carried out. Later, the data used will be validated in advance by the religious leaders concerned so that they can provide support that the stories told in this study do not deviate from the original teachings. The secondary data used is in the form of reference images, illustrations, clip art, animation, video or audio for making visual novel games via the internet. The result of this research is a Storytelling-based Visual Novel Game, where the story is taken from the Gospel of Matthew. In black box testing, this visual novel game shows that all functionality works well. In system usability scale testing, this visual novel game is categorized as good because it has an average value of 75,625.